(untitled) - Bailey, Alton Edward (Hoboken, N.J., 2005)
The second volume presents the main sources of food lipid oxidation and new articles on sesame oil and rice bran oil have been introduced
Keywords: Oils and fats,Công nghệ dầu ăn